The impact of work stress, work communication, and work discipline on employee performance at PT. Ferdinand Mandiri - Feberius Buulolo; Ferdinand A. Sm Hutapea; Merlina Nababan; Andre Fitriano; Tri Siwi Agustina (Privietlab, 2023)
This research is conducted with the background to achieve the author's objective, which is to study and describe the influence of work stress, work communication, and work discipline on employee performance at PT Ferdinand Mandiri. The results obtained by the researcher on the influence of work stress, work communication, and work discipline on employee performance in the company are not yet optimal. Therefore, research is carried out using scientific methods. The sample of this research uses the Slovin formula, thus obtaining 30 employees of PT Ferdinand Mandiri. The first process is done by measuring the sample data responses using validity tests and reliability tests. Subsequently, the test results are measured with classic assumption tests (normality test, multicollinearity test, heteroscedasticity test) and hypothesis tests using partial t-tests, simultaneous F tests, and multiple linear regression tests. The results of this study show that, partially, work communication and work discipline significantly influence the performance of employees at PT Ferdinand Mandiri. Meanwhile, work stress does not significantly affect the performance of employees at PT Ferdinand Mandiri. Simultaneously, work stress, work communication, and work discipline have a positive and significant simultaneous effect on the performance of employees at PT Ferdinand Mandiri.